An experimental study of two methods of problem-solving in arithmetic - Bayao, Areopagita T. 1932- (s.n.], 1968)
The author experimented on the two methods of problem solving in arithmetic, the whole method and the step-by-step method, to determine which of the two is more effective in developing the ability and skill in problem-solving of the students.